Discharge instability at early stage of plasma column formation in tokamaks - Azizov, E.A.; Barkalov, A.D.; Gladush, G.G.; Khayrutdinov, R.R. (Вопросы атомной науки и техники, 2003)
In our paper we study the breakdown physics and current rump in tokamaks in wide range of parameters in 0D model. It is shown that the current-voltage curves has the S-shape. If the loop voltage is greater than critical value than discharge goes from low-current stage to high-current stage. If voltage is less than critical value there are both dumping and steady-state oscillations with large amplitude. The breakdown voltage increased versus gas pressure and decreased versus minor plasma radius.